PERCEPÇÃO DOS USUÁRIOS PARA GESTÃO DA MANUTENÇÃO PREDIAL: ESTUDO DE CASO DE EDIFICAÇÃO RESIDENCIAL - Batista, Pedro Igor Bezerra; Pessoa, Rodrigo Gabriel Avelino de Queiroz; Póvoas, Yeda Vieira; Melhado, Silvio Burrattino (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This work aims to verify the perception of the users regarding the performance of the common areas of a residential building without a defined maintenance management plan. For this purpose, the Post-Occupancy Evaluation method (POE) was used to verify the users' opinion on the maintenance performance, the process consisted of six steps: Consultation of maintenance plan, selection of Elements Source of Maintenance (ESM's), inspection, questionnaire application, data analysis and generation of maintenance records. Seven ESMs were defined, and the two that presented the most indication of multiple problems were the common floor "T" (garage area) and elevators, both with 72.7%. The maintenance sheets have suggestions for actions and maintenance plans for each ESM. The absence of land maintenance management through an integrated plan of action leads to the appearance of pathological manifestations and a reduction in the performance of the systems of the common areas observed. The POE method proved to be an effective method for determining, through the managers, more efficient maintenance plans that focus on the need of the end users of the building, which raises their satisfaction and elevate the performance's level building, globally.